Implementation Plan in Response to Board-Endorsed Recommendations Arising from the IEO Evaluation of IMF Involvement in International Trade Policy Issues. (Policy Papers; Policy Paper ;, 2009)
This paper fulfils the requirement of a forward-looking implementation plan for Board-endorsed recommendations of the IEO Evaluation of IMF Involvement in International Trade Policy Issues ('the Evaluation'). The Evaluation and the Executive Board's conclusions provide impetus to re-prioritizing the Fund's trade policy work. Table 1 sets out the Evaluation's specific recommendations, Directors' responses to them, and the proposals for implementation within this framework. Directors called for recommendations to be implemented within the existing resource envelope-including by achieving closer and more effective cooperation with the WTO-and this implementation plan therefore does not provide detailed costing of individual items.